(3cJGH GdeQTOs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s ((3eMeO Hf bWH GdWHjH s)
(3ChdgG (B:s
(3bGd GdMcje OYGfi eG hLOJ Ydjg aUhd HbQGW ef GdGNJdGa hYOe GdfXGe hGdZehV hGdJbUj Yf PcQ LhGeY GdUfGYI cdgG Ch LdgG s
(3BNQgG (B:s
(3ai cd fhY ef GdYdd hMaX GdUMI hGdRjfI ef JYQja Gh SHH Gh JbSje bO PcQfG GdcKjQ eeG MVQfG ef Led UfGYI GdWH s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3jdjgG UaMI HgG ahGFOs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs